SUCCESS, FOLLY, AND FAILURE: SOME PAULINE JUDGEMENTS REGARDING THE FORMATION OF CHRISTIAN SOCIAL IDENTITY - Conroy, Joshua D. (My University, 2018)
This thesis seeks to answer questions regarding Paul’s understanding of Christian identity by arguing that Paul views Christian identity as a superordinate or New Human identity in which many previous identities persist as subordinate identities, transformed by the superordinate Christian identity—although some previous identities must cease as they are not compatible with the superordinate Christian identity. Utilizing the combined approaches of Social Identity Theory and Self-Categorization Theory, I describe the perspectives that Paul presents in his correspondence with the Thessalonians, Galatians and Corinthians. As regards the Thessalonians, Paul observes that the Thessalonians succeeded in adopting Christian identity. In comparison, the Galatians, while recognizing their need for transforming their subordinate identities, are foolishly attempting to adopt a Judean identity. Finally, Paul rebukes the Corinthians for failing to appropriately adopt Christian identity and for choosing instead to continue to live according to their Old Human identity.
Keywords: Paul; Christian Identity; New Human Identity; Social Identity Theory; Self-Categorization Theory; Old Human Identity